A chimeric PCV rescued virus with the immunogenic cap gene of PCV3 cloned into the genomic backbone of the nonpathogenic PCV1 induces specific antibodies but with no pathogenic in pigs. (December 2022) - Shi, Jianli; Wu, Xiaoyan; Wang, Shuo; Li, Jiaxin; Wang, Zhao; Yang, Ying; Peng, Zhe; Liu, Chang; Xu, Shaojian; Li, Chen; Tian, Yao; Han, Hong; et al.
Abstract: A chimeric PCV called PCV1-3 with the immunogenic Cap gene of pathogenic PCV type 3(PCV3) cloned into the genomic skeleton of the nonpathogenic PCV1 was rescued and inoculated into PCV3 negative piglets. The results of fluorescence quantitative PCR showed that the PCV1-3 DNA detected in serum and tissues was negative. The pathogenicity of piglets showed that PCV 1–3 did not cause the clinical characteristics and pathological changes. The viral neutralization assay revealed that infected pigs could produce antibodies and neutralize the viral activity. All results showed that chimeric virus induced specific antibodies but with no pathogenic in pigs, which provided new candidate strains for the development of PCV3 vaccine. Highlights: A chimeric PCV with the immunogenic capsid gene of pathogenic PCV3 cloned into the genomic backbone of PCV1 could be rescued. The chimeric PCV 1–3 virus did not cause the clinical characteristics and pathological. The infected pigs could produce antibodies and neutralize the viral activity.